Do Visko ao vício: Alessandro Boffa e a fabulação do riso em "Você é um animal, Viskovitz" - Alves, Julio (Universidade Federal de São Carlos, 2025)
Modern fables often use zoopoetics to question human conventions, distancing themselves from the explicit morality characteristic of classical models. Topics dear to contemporary society, such as social gender roles, can be addressed in a less direct manner when related to the human context. This dissertation aims to analyze the construction and function of laughter in the work You’re an animal, Viskovitz (1999), by Alessandro Boffa, a writer and biologist, based on the premise that his zoo(auto)biographical narrative uses laughter to encourage reflections on animal otherness and gender norms. Through a theoretical framework centered on Sigmund Freud and Arthur Schopenhauer's perspectives on the laughable and the comic, short stories from the work are examined based on unconscious structures, language, and subjective constitution. The analysis demonstrates that the friction between ethological precision and the projection of human conflicts generates a zone of productive incongruity, eliciting both laughter and critical reflection in the reader. The male narrator, who is repeatedly flawed, serves as a vehicle for an ironic critique of male chauvinism, narcissism, and the patriarchal system that socially and culturally structures gender relations. Philosophical, scientific, and religious reflections are added to the debate on gender. It is concluded that Boffa's literary project uses laughter as an instrument of knowledge and transformation of the reader's gaze, revealing social contradictions and existential dilemmas.
From Visko to Vice: Alessandro Boffa and the fabulation of laughter in “You're an Animal, Viskovitz”
Keywords: Literatura italiana; Fábulas modernas; Riso; Relações de gênero; Alessandro Boffa; Italian literature; Modern fables; Laughter; Gender relations; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS